Assessment of the severity of nausea and vomiting among women during pregnancy vs. selected risk factors - Cisek, Anna; Bucholc, Marzena (Polish Journal of Public Health, 2016)
Introduction. It is estimated that 90% of pregnant women suffer from nausea and vomiting (NVP). The severity of NVP may vary and the first symptoms tend to appear between the 4th and 9th week of pregnancy, reaching their peak around 7th-12th week and disappear around 16th-20th week of pregnancy. The etiology of both nausea and vomiting is yet to be discovered, yet there is a number of factors that may contribute to it. These symptoms usually accompany the increase of human chorionic gonadotropin (hCG) and most intensive ailments associated to the highest rate of this hormone appear around the 10th week of pregnancy. Aim. Assessing the severity of nausea and vomiting in pregnant women and selected risk factors. Material and methods. The study group consisted of 150 women hospitalized in the Independent Public Teaching Hospital No 4 in Lublin. The head of the Department of Obstetrics and Perinatology Agreement has agreed for the studies to be conducted. The authors used a research tool named modified scale Pregnancy Unique Quantification of Emesis which allowed to investigate the incidence and severity of nausea and vomiting during pregnancy. Demographic data and information on the conditions of nausea and vomiting in pregnancy were collected using a questionnaire survey of the authors’ own making. Database and statistical tests were conducted using 10.0 STATISTICA software (StatSoft, Poland). Results. The analysis revealed that 108 women (72.00%) experienced nausea or vomitting during pregnancy. Taking into consideration the first trimester of pregnancy, a moderate severity of nausea and vomiting (NVP) occurred with an average of 6.51±3.17 pt. It was found that 82 respondents had light intensity of NVP, whereas 68 moderate. In the second trimester an average intensity of nausea and vomiting (NVP) came to 4.82±2.45 pt, i.e. 117 women had mild symptoms while 33 had moderate symptoms. During the third trimester NVP severity dropped to 3.88±1.67. The majority of respondents stated that nausea and vomiting was of light intensity (92.00%), while 8% declared that it was moderate. Conclusions. The severity of nausea and/or vomiting varies in the course of pregnancy, with significantly more moderate than mild symptoms occurring in the first compared to other trimesters of gestation. The degree of the severity of NVP in the third trimester of pregnancy is significantly affected by risk factors occurring before pregnancy (migraine headache, nausea or vomiting), and comorbidities. However, the number of pregnancies, the fact whether the pregnancy was planned or not, motion sickness do not have major significance in this matter.